Kajian Tentang Kesamaan Pakan Herbivora Dengan Pendekatan Analisis Kotoran - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1995)
ABSTRACT Herbivore's food competition presumably occurred in Baluran National Park, East Java was studied using faecal analysis method. Through the method, plarit epidermal fragments found in faecal remnants of three large ungulates, namely banteng, feral buffalo and rusa deer were identified by comparison with a reference-collection. Their respective dominant diet may then be compared to analyze the dietary overlap as a approach towards studying their food corn-petition. The study has shown that dietary overlap values vary below and above the critical value of competition and further provide evidences about food competition between studied ungulates which ultimately suggest that food partitioning is likely to occur rather than competition. Besides, the study reveal that the use of faecal analysis method in order to investigate such presumed competition is of considerable help